Underscreened Women Remain Overrepresented in the Pool of Cervical Cancer Cases in Spain: A Need to Rethink the Screening Interventions. (9th June 2015) - Ibáñez, Raquel; Alejo, María; Combalia, Neus; Tarroch, Xavier; Autonell, Josefina; Codina, Laia; Culubret, Montserrat; Bosch, Francesc Xavier; de Sanjosé, Silvia
Abstract : Objective . Audit of women with invasive cervical cancer (CC) is critical for quality control within screening activities. We analysed the screening history in the 10 years preceding the study entry in women with and without CC during 2000–2011. Methods . 323 women with CC from six pathology departments in Catalonia (Spain) and 23, 782 women with negative cytology were compared. Age, previous history of cytologies, and histological type and FIGO stage were collected from the pathology registries. Logistic regression analysis was used to estimate odds ratios (OR) and 95% confidence intervals (CI95%). Results . History of cytology was registered in 26.2% of CC cases and in 78% of the control women (P < 0.0001 ) and its frequency decreased with increasing age. Compared to women with squamous cell carcinoma, adenocarcinoma cases were significantly more likely to have a cytology within the 3-year interval preceding cancer diagnosis (OR = 2.6 CI 95%: 1.2–5.6) and to have normal cytology results in previous screenings (OR = 2.4 CI 95%: 1.2–4.5). FIGO II–IV cases were more common among older women (older than 60 years). Conclusions . Absence of prior screening history was extremely common among CC cases compared to controls. Organized actions to reduce underscreened women and use of highly sensitive HPV-based tests could be important to reduce CC burden.